2006
DOI: 10.4049/jimmunol.177.6.4149
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 Participation in Th Type 1 (Mycobacterial) and Th Type 2 (Schistosomal) Anamnestic Pulmonary Granulomatous Responses

Abstract: CCR4 is purported to be a Th type 2 (Th2) cell-biased receptor but its functional role is unclear. Recent studies suggest that chemokine receptor expression and function are more complex in vivo and raise doubts regarding restricted CCR4 expression by Th2 cells. To address these issues, we analyzed the role of CCR4 in highly polarized models of Th type 1 (Th1) and Th2 cell-mediated pulmonary granulomas, respectively, elicited by i.v. challenge of primed mice with either mycobacterial purified protein derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
2
22
0
1
Order By: Relevance
“…3 This finding was unexpected and provided further evidence that CCR4 expression and function were not restricted to Th2 cells. However, the role of CCR4 in the lung response to a live mycobacterial agent was unknown.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…3 This finding was unexpected and provided further evidence that CCR4 expression and function were not restricted to Th2 cells. However, the role of CCR4 in the lung response to a live mycobacterial agent was unknown.…”
mentioning
confidence: 52%
“…2 We demonstrated that CCR4ϩ Th1 and Th2 cells were detected in mouse models of Th1 and Th2 cell-mediated pulmonary granulomatous inflammation, respectively, elicited by mycobacterial and helminth antigens. 3 In a detailed analysis 4 of human peripheral blood T cells, CCR4 expression was detected on isolated human CD4 ϩ memory T cells with Th1 and Th2 characteristics. The specific ligands for CCR4, cysteine-cysteinyl ligan (CCL)17, and CCL22 induced migration of both Th1 and Th2 cells in vitro.…”
mentioning
confidence: 99%
“…23,24,26 Purified airway luminal and granuloma cells were stained with antibodies against CD3, CD4, CD8, CD19, CD11c, Gr.1, CD11b, or NK1.1 and analyzed by FACS. The FACS analysis revealed the presence of CD3ϩCD4 ϩ (CD4 T cells), CD3ϩCD8ϩ (CD8 T cells), CD3-CD19ϩ (B cells), CD3-NK1.1ϩ [natural killer (NK) cells], CD11cϩ-CD11bϩ/Ϫ (CD11cϩ APCs), CD11c-CD11bϩ (CD11bϩ APCs), and CD11c-Gr.1ϩ (neutrophils) cell populations in both the airway lumen and granuloma (Table 1).…”
Section: Similar Immune Cellular Composition Observed In Airway Lumenmentioning
confidence: 99%
“…It has also been found that mRNA of CCL17 and its receptor CCR4 are primarily expressed in lesional skin of atopic dogs and are not detected in non-lesional canine skin [15]. Although the CCR4 receptor is preferentially expressed on T H 2 cells, other subsets including activated T H 1 cells have displayed expression of the same receptor [6].…”
mentioning
confidence: 96%